How do we perceive autistic individuals in a non-social context? - Jaffrani, Asiya Ayoob (2022)
This thesis aimed to investigate how autistic individuals are perceived by non-autistic individuals in the absence of a social context. An experimental paradigm was developed and piloted in order to test retrodictive mindreading (Chapter 2). The paradigm had a target phase, in which behavioural stimuli were created (in a non-social context), and a perceiver phase, in which judgments were made regarding the behavioural stimuli. Findings suggested that people do emit observable behavioural signals, while recalling their memories in response to cue words. The same paradigm was used in Chapter 3 to investigate differences between autistic and neurotypical targets in measures of readability, social favourability, and expressiveness from neurotypical perceivers. Findings revealed that perceivers were able to make accurate inferences about autistic behaviour and, in some cases, were better at inferring autistic behaviour when compared to the neurotypical behaviour. These findings were consistent in perceivers of different age groups. Autistic targets were also judged to be more expressive than the neurotypicals. However, in terms of social favourability ratings, autistic individuals were less liked than the neurotypical individuals by perceivers from three age groups: 10-12 years, adults and older adults. No evidence was found that autistic individuals were less liked by children aged between four to nine years. In Chapter 4, two studies were carried out to investigate a range of aspects of the written narratives of autistic and neurotypical targets while writing about emotional experiences. While the first study focused only on the numbers of words used of different types, the second study aimed to investigate more holistic differences in the quality of autistic and neurotypical writings. Findings suggested that autistic individuals’ narratives have many similarities but also some differences from neurotypical individuals' narratives in the quality and the structural aspects of writing. Autistic individuals even seemed to be better on some of the measures. In Chapter 5, the study aimed to investigate whether people can correctly guess autism diagnosis from watching brief samples of behaviour or from reading narratives that describe their emotional experiences. The study also looked at the effect of diagnostic disclosure on social favourability ratings. Findings indicated that although perceivers tended to judge that targets are neurotypical as opposed to autistic, nevertheless to some extent autistic individuals can be distinguished based on their behaviours and also from written excerpts that describe their life experiences. Furthermore, when informed that some targets were autistic, perceivers rated all targets to be less likeable compared to the condition when no diagnostic was used. This suggested that people seem to have a negative (implicit) attitude or stigma towards autistic individuals that influences their judgments. In conclusion, this work suggests people may not find it difficult to accurately perceive autistic individuals when a social context is not involved and using text as a means of communication with the non-autistic individuals may protect autistic individuals from being affected by the negative perceptions of the non-autistic individuals.